Revisiting Persistent Neuronal Activity During Covert Spatial Attention - Amengual, Julian L.; Ben Hamed, Suliann (Frontiers in Neural Circuits, 2021)
Persistent activity has been observed in the prefrontal cortex, in particular during delay periods of visual attention tasks. Classical approaches based on averaged activity over multiple trials have revealed that such activity encodes information about the attentional instruction provided in such tasks. However, single-trial approaches have shown that activity in this area is rather sparse than persistent and highly heterogeneous within trial but also between different trials. This observation thus contributes to the question of how persistent is actually persistent attention-related prefrontal activity. In this paper we review novel evidence that precisely deconstructs the persistence of the neural activity of the prefrontal cortex in the context of orienting of attention. The inclusion of machine-learning methods to decode information reveals that orienting of attention is a highly dynamic process with an intrinsic oscillatory dynamics working at multiple time-scales spanning from milliseconds to minutes. Dimensionality reduction methods further show that this persistent activity dynamically incorporates multiple sources of information. This novel framework reflects the high complexity of the neural representation of the attention-related information in the prefrontal cortex, and how its computational organisation predicts behaviour.